Impact of Frequency Variations in Ultrasonic Transducers on Material Properties - Maiyena, Sri; Ayop, Shahrul Kadri; Mat Daud, Anis Nazihah (Lambung Mangkurat University Press, 2024)
Research has been carried out to determine material properties using ultrasonic waves. The aim of the research is to see the effect of variations in ultrasonic transducer frequency on material properties, material mechanical properties and material acoustic properties. The ultrasonic technique used is based on the pulse echo technique. The samples used were steel with a thickness of 2.5 cm, aluminum with a thickness of 2 cm and 1.8 cm and PMMA with a thickness of 1.5 cm, 1 cm and 0.2 cm. There are three variations of transducer frequency used, namely 2.25 MHz, 5 MHz and 10 MHz. The mechanical property of the material that will be determined is the elastic modulus. The acoustic properties of the material to be determined are longitudinal velocity, attenuation coefficient and acoustic impedance. The results showed that variations in transducer frequency did not affect the values of elastic modulus, longitudinal velocity and acoustic impedance. However, the use of transducer frequency variations affects the attenuation coefficient value.